Spatial variability of dendrometric parameters in a native tree Mabea fistulifera Mart. and its relationship with soil physical properties - Ferreira Cortes, Alessandra; Lima Sampaio, Ana Patrícia; Rojas Plazas, Gloria Milena; da Costa, Carlos Matheus Santos [UNESP]; Montanari, Rafael [UNESP]; de Oliveira, Job Teixeira (Universidad Nacional de Colombia, 2023)
Mabea fistulifera Mart. (common name: canudo-de-pito) be-longs to the Euphorbiaceae family and is a native tree species in Brazil showing a high potential to recover degraded lands. This study aimed to evaluate the distribution and spatial correlation between the dendrometric parameters of the M. fistulifera plants and the physical attributes of the soil through geostatistics. The study was carried out at the Paulista State University (UNESP), in the city of Selvíria, MS, Brazil, in a typical dystrophic Red Oxisol with a clayey texture. The following properties were analyzed: for soil, penetration resistance, gravimetric moisture, particle density, and, for plants, circumference and diameter at breast height (measured at 130 cm above the ground), tree height, and total volume of the tree. An experiment grid was introduced with 35 sample points spaced 13 m x 13 m. Two soil samples were taken at each point, at 0.00-0.10 m, and 0.10-0.20 m depth. Descriptive data analysis and spatial dependence analysis were carried out through semivariogram adjustments and kriging maps. The dendrometric properties of the species M. fistulifera and the soil gravimetric moisture content showed spatial dependence. The spherical semivariogram model best explained the spatial structure of circumference at breast height, diameter at breast height, tree volume, and soil gravimetric moisture. There was an emphasis on the correlation between the total volume of the tree as a function of the diameter at breast height, showing a moderate spatial dependence. Furthermore, the tree diameter at breast height proved to be a good indicator for determining the total height of the M. fistulifera tree.
Variabilidad espacial de parámetros dendrométricos del árbol nativo Mabea fistulifera Mart. y su relación con las propiedades físicas del suelo
Keywords: canudo-de-pito; geostatistics; kriging maps; precision agriculture